Reviewer Acknowledgements: GHMJ (Global Health Management Journal), Volume 7, Editions 1, 2, and 3, 2024 - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal), 2024)
GHMJ (Global Health Management Journal) is proud to announce the successful publication of 18 high-quality articles across the first, second, and third editions of its seventh year. Each published article represents the culmination of a rigorous process, including a double-blind peer review conducted by our Editorial Board and carefully selected reviewers, chosen for their expertise in the field of global health. We extend our deepest gratitude to the distinguished scholars and professionals who contributed their time, knowledge, and insights to reviewing the manuscripts for these issues. Their dedication and commitment to academic excellence have been essential in maintaining the high standards of our journal. Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Journal Managers Suyitno, M.PHM Maretalinia, M.A External Reviewers Ratih Yulistika Utami, MMedEd. (Universitas Muhammadiyah Sumatera Utara, Indonesia) Uswatun Khasanah, M.Pd., MKM. (Universitas Swadaya Gunung Jati, Indonesia) Donny Nauphar, M.Si.Med. (Universitas Swadaya Gunung Jati, Indonesia) Associate Prof. Dr. Md Azalanshah Bin Md Syed (University of Malaya, Malaysia) Crossman Mayavo, Ph.D (University of Johannesburg, South Africa) Erwiantono, M.Si. (Universitas Mulawarman, Indonesia) Melyana Nurul Widyawati, M.Kes. (Poltekkes Kemenkes Semarang, Indonesia) GHMJ (Global Health Management Journal) invites scholars and professionals to contribute to enhancing the quality of our publications. If you are interested in serving as a reviewer, we warmly welcome your participation. To join us, please register on our website and select the "Reviewer" option during the registration process. Benefits of Becoming a Reviewer: Receive formal recognition by having your name listed as a Reviewer in each edition you contribute to. Gain opportunities for professional growth by being considered for inclusion on the Editorial Board in future editions. Reviewers will enjoy an exclusive opportunity to publish Editorial Papers with us at no cost. Acceptance Rate                            : 45%  Days to First Editorial Decision : 17 days Days to accept                                : 73 days     Published : 21 November 2024.